COMPARISON OF BLOOD TRANSFUSION REQUIREMENT IN PATIENTS UNDERGOING TOTAL HIP REPLACEMENT WITH AND WITHOUT INTRAVENOUS TRANEXAMIC ACID: RANDOMIZED CONTROL TRIAL (The Research of Medical Science Review, 2025)
Background: Total hip replacement (THR) surgery is often associated with significant blood loss, necessitating blood transfusions. Tranexamic acid (TXA), an anti-fibrinolytic agent, has shown promise in reducing blood loss during THR surgery. However, concerns about its safety have limited its widespread adoption. Objectives: This randomized controlled trial aimed to compare the frequency of blood transfusion requirements in patients undergoing THR surgery with and without TXA administration. Methods: A total of 122 patients were randomly assigned to receive either TXA (15 mg/kg, 5 minutes before incision) or no TXA. Patients' demographics, hemoglobin levels, and blood transfusion requirements were recorded and analyzed. Results: The study found a statistically significant reduction in blood transfusion requirements in the TXA group compared to the no TXA group (4.9% vs. 23.0%, p-value = 0.004). The TXA group also demonstrated a lower mean hemoglobin drop post-surgery. Conclusion: This study provides evidence that TXA administration is a safe and effective strategy for reducing blood transfusion requirements after THR surgery. The findings support the use of TXA as a standard practice in THR surgery to minimize blood loss and transfusion-related complications. Further studies are needed to confirm these results and establish the optimal dosage and administration protocol for TXA in THR surgery.